2018
DOI: 10.1111/jvh.12855
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir and tenofovir reduce hepatitis B virus‐related hepatocellular carcinoma recurrence more effectively than other antivirals

Abstract: Nucleos(t)ide analogues (NAs) have been shown to decrease the risk of hepatocellular carcinoma (HCC) recurrence. This study evaluated whether high-potency NAs (entecavir and tenofovir disoproxil fumarate [TDF]) reduce the risk of tumour recurrence more potently than low-potency NAs after curative treatment of hepatitis B virus (HBV)-related HCC. This study included 607 consecutive HBV-related HCC patients treated with surgical resection or radiofrequency ablation. The patients were categorized into three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…A meta-analysis showed that the antiviral treatment group had significantly lower risk of tumor recurrence (odds ratio [OR], 0.59; 95% confidence interval [CI], 0.35–0.97; P =0.04), liver-related mortality (OR, 0.13; 95% CI, 0.02–0.69; P =0.02), and overall mortality (OR, 0.27; 95% CI, 0.14–0.50; P <0.001), than the no antiviral treatment group [368]. In a retrospective Korean study, antiviral treatment with high-potency NAs (i.e., entecavir and tenofovir) showed significantly longer recurrence-free survival than both antiviral treatment with lowpotency NAs (i.e., lamivudine, clevudine, and telbivudine) and no antiviral treatment [369]. In contrast, a randomized controlled trial reported that adjuvant interferon alfa-2b treatment was not associated with lower risk of post-resection tumor recurrence ( P =0.828) [370].…”
Section: Management In Special Conditionsmentioning
confidence: 99%
“…A meta-analysis showed that the antiviral treatment group had significantly lower risk of tumor recurrence (odds ratio [OR], 0.59; 95% confidence interval [CI], 0.35–0.97; P =0.04), liver-related mortality (OR, 0.13; 95% CI, 0.02–0.69; P =0.02), and overall mortality (OR, 0.27; 95% CI, 0.14–0.50; P <0.001), than the no antiviral treatment group [368]. In a retrospective Korean study, antiviral treatment with high-potency NAs (i.e., entecavir and tenofovir) showed significantly longer recurrence-free survival than both antiviral treatment with lowpotency NAs (i.e., lamivudine, clevudine, and telbivudine) and no antiviral treatment [369]. In contrast, a randomized controlled trial reported that adjuvant interferon alfa-2b treatment was not associated with lower risk of post-resection tumor recurrence ( P =0.828) [370].…”
Section: Management In Special Conditionsmentioning
confidence: 99%
“…Then, Kim et al showed that overall survival and recurrence-free survival were better in the ETV-treated patients than in the LAM treated-patients, indicating that the potent antiviral drug should be the preferred choice in HBV-related HCC patients in 2016 47. Cho et al reported that antiviral agents with high genetic barrier to resistance (ETV and TDF) reduced the risk of HCC recurrence compared with other antivirals and no antiviral treatment, especially in patients with high baseline viral load in 2018 48. However, there are conflicting or ambiguous views on the difference of therapeutic outcomes between nucleoside analogs and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Antiviral therapy using interferons or nucleos(t)ide analogs (NAs) efficiently reduces these risks by suppressing HBV replication. [25][26][27][28][29] Current guidelines recommend treatment initiation with antiviral agents before the accumulation of liver injury or progression of fibrosis. However, intrahepatic covalently closed circular DNA cannot be eradicated, even with long-term treatment.…”
Section: When To Start: Comparison Of Treat-ment Indicatorsmentioning
confidence: 99%
“…Antiviral treatment during the immune active phase decreases the risk of liver cirrhosis, hepatic decompensation, and HCC. [25][26][27][28][29] Therefore, antiviral therapy is recommended for patients in this phase. The criteria for treatment differ slightly among the guidelines ( Table 3).…”
Section: Chb Immune Active Phasementioning
confidence: 99%
See 1 more Smart Citation